PENGARUH KONSENTRASI GELATIN DAN GULA TERHADAP SIFAT FISIKOKIMIA DAN ORGANOLEPTIK PANNA COTTA - Handani, Yohana; Sutedja, Anita Maya; Trisnawati, Chatarina Yayuk (Jurnal Teknologi Pangan dan Gizi, 2016)
Panna cotta is an Italian dessert made from heavy whipping cream, milk, gelatin and sugar. The formula of panna cotta in Italia is less suitable to be applied in Indonesia because heavy whipping cream is unavailable in Indonesia and people don’t like thick cream. Replacement of heavy whipping cream with light whipping cream and change in light whipping cream-milk ratio into 1:9 were done to adjust panna cotta with the preference of panelist. This affected to the concentration of gelatin and sugar should be added. The purpose of this study was to determine the effect of gelatin and sugar concentration and their interaction on the characteristic of panna cotta. The research design used was a factorial randomized block design that consists of two factors: the concentration of gelatin (1%; 1,25%; and 1,5%) and the concentration of sugar (2,5%; 5%; and 7,5%) to obtain nine combination treatment and replicated three times. Analysis of panna cotta included physical properties (color, syneresis, and texture: hardness), chemical properties (moisture content and total dissolved solids), and the sensory properties based on hedonic test (gel firmness, ease to melt, taste, ease to swallow and color). Data were analyzed using ANOVA test at α = 5%, if the results showed a significant effect, data were analyzed by followed by Duncan’s Multiple Range Test at α = 5% to determine the combination treatment that gave a significant difference. The results indicated interactions between gelatin and sugar concentration provided significant effect on texture (hardness) of panna cotta. Increasing concentration of gelatin caused a decreased in moisture content, syneresis, lightness and ohue, but redness and yellowness increased. Increasing concentration of sugar caused a decreased in moisture content, syneresis, lightness and redness, but total dissolved solids and ohue increased. The treatment recommended was 1% gelatin and 7,5% sugar.